Decomposition of hydrogen solution in the neighborhood of the coolant saturation temperature as a possible cause of increased oxidation of VVER fuel element. (1st December 2022) - Ivanov, A.S.; Kovalishin, A.A.; Kalashnikova, P.A.; Taran, M.D.
Abstract: The analysis carried out in this work has shown that a sharp local decrease in the hydrogen concentration and a corresponding increase in the radiolytic oxygen content is caused by two phase transitions occurring in the reactor coolant at successive temperatures. Decomposition of hydrogen solution in the coolant in the neighborhood of the saturation temperature is followed by the liquid–vapor phase transformation. In this case, the coolant may in some zones deviate from the strict water-chemistry regime aimed to suppress radiolysis. It has been shown that the hydrogen concentration in the coolant may decrease by orders of magnitude in a short time. In this case the efficiency of radiolytic oxygen suppression reduces drastically, and concentration of the radiolytic oxygen in the coolant may increase considerably, thus promoting local oxidation of VVER fuel element claddings in E110. Highlights: Decrease in the hydrogen content it leads to increase in the oxygen content. It is leads to oxide layer build-up on the surfaces of VVER fuel element claddings. The coolant may in some zones deviate from the strict water-chemistry regime. The efficiency of radiolytic oxygen suppression reduces drastically. It is promoting local oxidation of fuel element claddings.